Evaluation Report on Integrated Child Development Services Volume II (Appendix) - Planning Commission (Planning Commission, 2011)
State-wise Status of Filled-in Institutional Level Questionnaires (%) State-wise Sample Profile for ICDS- 2009 Estimated Effective Coverage in Supplementary Nutrition Programme for Children Under ICDS Status of Effective Coverage of Supplementary Nutrition Programme for Children Status of Effective Coverage of Supplementary Nutrition Programme for Pregnant Women & Lactating Mothers Status of Effective Coverage of Supplementary Nutrition Programme for Adolescent Girls Projected Shortfall/excess of AWCs by States Percentage of AWC Having Type of Housing Facility Percentage of AWC Have Adequacy of Space for Different Type of Activities Area of the Room Where Beneficiary Sit Percentage of AWC Having Source of Drinking Water Percentage of AWC Having Source of Drinking Water According to Distance Percentage of AWC Having Toilet Facilities Percentage of AWC Having Weighing Scales and Other Inventories Percentage of AWCs Providing Different Types of Services Reported by the AWW Average Daily Time Spent By AWW (In Minutes) Percentage of AWW Involved In Other Government Scheme during Last Year Percentage of AWW Reporting Regularity of Visits of ANM.
Programme Evaluation Organisation Planning Commission Government of India